2003
DOI: 10.1128/jcm.41.9.4172-4177.2003
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Seminested PCR for Detection and Differentiation ofBabesia gibsoni(Asian Genotype) andB. canisDNA in Canine Blood Samples

Abstract: Canine babesiosis has recently been recognized as an emerging infectious disease of dogs in North America. We sought to develop a seminested PCR to detect and differentiate Babesia gibsoni (Asian genotype), B. canis subsp. vogeli, B. canis subsp. canis, and B. canis subsp. rossi DNA in canine blood samples. An outer primer pair was designed to amplify an ϳ340-bp fragment of the 18S rRNA genes from B. gibsoni (Asian genotype), B. canis subsp. vogeli, B. canis subsp. rossi, and B. canis subsp. canis but not mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
292
1
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(307 citation statements)
references
References 25 publications
6
292
1
8
Order By: Relevance
“…This is in agreement with Matsuu et al (2005) who reported detection limit of light microscopy as approximately 0.001 % parasitaemia compared to PCR capable of detecting 9 parasites per ll of blood similar to 50 organisms/ml of blood reported by Birkenheuer et al (2003).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This is in agreement with Matsuu et al (2005) who reported detection limit of light microscopy as approximately 0.001 % parasitaemia compared to PCR capable of detecting 9 parasites per ll of blood similar to 50 organisms/ml of blood reported by Birkenheuer et al (2003).…”
Section: Resultssupporting
confidence: 81%
“…So 17.12 % cases remained false negative to Babesia during microscopy. Higher detection of Babesia in PCR compared to microscopy as observed in the present study was also reported by several authors (Birkenheuer et al 2003;Gotsch et al 2009;O'Dwyer et al 2009). The prevalence pattern of this two species recorded in the present study was found similar to those microscopic and serologic findings reported by other workers (Bansal et al 1985;Varshney et al 2003;Senthil Kumar et al 2009).…”
Section: Resultssupporting
confidence: 78%
“…Para isto foram utilizados os oligonucleotídeos GAPDH-F (5'-CCT TCA TTG ACC TCA ACT ACA T-3') e GAPDH-R (5'-CCA AAG TTG TCA TGG ATGACC-3') que anelam em uma seqüência especíϐica do gene da enzima gliceraldeído 3-fosfato desidrogenase e resulta em um produto de 400 pb (Birkenheuer et al 2003 Doyle et al (2005). Para a identiϐicação de A. platys foi utilizada a nested polymerase chain reaction (nPCR) foi realizada como descrito por Martin et al (2005), usando oligonucleotídeos 8F ( 5' AGT TTG ATC ATG GCT CAG 3') e 1448R (5' CCA TGG CGT GAC GGG CAG TGT G 3'), que ampliϐica a maior parte do gene 16S rRNA (Dawson et al 1996), na primeira etapa da PCR.…”
Section: Methodsunclassified
“…The absence of PCR inhibitors was demonstrated by the amplification of a fragment of the constitutive gene for the glyceraldehyde-3-phosphate dehydrogenase (GAPDH) protein, an enzyme related to the glycolysis pathway that is expressed in all mammal cells [5,7].…”
Section: Dna Extractionmentioning
confidence: 99%